Anti-Mullerian Hormone as a Marker for Enhanced Reproductive Strategies in Buffaloes Vis-à-vis Cattle: A Review - Sharma, Prachi; N Saripadiya, Bhautik; K Hadiya, Kamlesh; N Patel , Chirayu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Buffaloes, comprising the River and Swamp sub-species, hold increasing importance in tropical and subtropical regions due to their  ecological adaptability and economic benefits. However, their reproductive physiology, particularly ovarian follicular dynamics, differs  from cattle, posing challenges for assisted reproductive technologies (ART). This review explores the role of the anti-Mullerian hormone  (AMH) as a potential marker for ovarian reserve, ART outcomes, and fertility in buffaloes. Comparative studies with cattle highlight  differences in follicular populations and AMH levels. AMH emerges as a promising marker for predicting superovulatory response,  embryo production efficiency, and fertility across different stages of reproductive aging. Molecular insights into the AMH gene shed  light on its genetic regulation and evolutionary significance in various domestic species. Understanding the role of AMH in buffalo  reproductive biology offers avenues for optimizing ART protocols and genetic improvement strategies, thus enhancing the sustainability  and profitability of buffalo breeding programs.
Keywords: Anti-Mullerian hormone; ART; OPU-IVEP; Ovarian reserve; Biomarker; Buffalo